Game and ludic on Martial Arts content in physical education classes - So, Marcos Roberto (2020)
The pedagogical treatment of the martial arts content causes difficulties and tensions between teachers and students. It is important to ask: what is the meaning given to the mobilization and the activities of students in martial art games? The aim of this paper is to discuss the influence that games have on mobilization and meanings of martial art content from the student's perspective. This is a case study with a 7th grade middle school classroom the methodological procedures were: (a) observation of Judo classes, and (b) semi-structured interviews with students before and after the sequence of classes. From classes observation, we realized that the teacher used martial art games which were appropriate to minimize the feeling of fear, anxiety, and stress related to getting hurt during the practice. In addition, the fun and playfulness provided by the games promoted a dissociation of martial arts from violence and fighting the immersion and absorption of students in martial arts games have promoted the end of stereotyped initial impressions of martial arts (e.g. martial arts hurts, it is violent, etc.), taking them to a fantasy game world. In this way, games proved to be essential for the pedagogical approach to martial arts content, especially by promoting students' participation.